Increasing Water Resources Availability Under Climate Change. (2016) - Beran, Adam; Hanel, Martin; Nesládková, Magdalena; Vizina, Adam
Abstract: The attention to the water scarcity problems caused by climate change is paid in the Czech Republic since 1990's. Increasing daily mean temperature, changes in distribution of precipitation and earlier snow melt lead to insufficient recharge of the groundwater reserves and in turn to a decrease of baseflow component of total runoff. Water streams are then more sensitive to drying during dry periods, which has far-reaching impacts on water stream ecology and the availability of water for the users. The paper describes objectives, methods and first year results of the project 'Increasing water resources availability in selected regions of Karlovy Vary district'. The project is focused on the region that faces long term problems with water availability. The objective is a development and verification of methods for proposal of adaptation measures to increase the reliability of water resources in the periods of water stress.